Post-Stroke Complications and Consequences among the Patients in Dhaka Medical College Hospital - Uddin, Md Minhaz; Ridita, Sadia Shahid; Hoque, Zahedul; Jabed, Syed Md; Zahed, Noor Uddin; Hassan, Nahid; Habib, Mansur (IAHS Medical Journal, 2025)
Background: Medical complications are important problems after acute stroke and present potential barriers to optimal recovery. Sometimes patients die not from stroke but from complications. Several studies have underwent regarding this topic. However, considering fewer studies in this country incites the mind to perform a prospective study of assessing the complications and outcomes among post-stroke patients admitted to Dhaka Medical College Hospital (DMCH). Materials and methods: This cross-sectional study was carried out at the DMCH's Department of Medicine and Neurology during 2018-2019 period. The study had a six-month duration and formal ethical approval was obtained from the DMC Ethical Review Committee (ERC) prior to study initiation. For the purpose of this study, patients who had been admitted to DMCH due to an acute stroke were approached and monitored for a period of seven days. All clinical data, vital signs and sociodemographic details were gathered at the time of admission. Additionally, co morbidities and risk factors were entered into a case record form. 200 post-stroke patients were selected as case. Every participant provided written, informed consent and the entire study was conducted under strict adherence to ethical guidelines. After data collection, SPSS version 20 was used to analyze the data. Results: Among 200 acute stroke patients, the Majority (66%) of the respondents were male and 34% were female. The mean age was 59.62±12.02 years, with a minimum recorded age of 35 years and a maximum recorded age of 83 years. About 54% lived in urban areas and 46% were in rural areas. About 90% had ischemic stroke and 10% had hemorrhagic stroke. Among the medical complication, chest infection was the most prevalent 91(46%) and among neurological complication, seizures were the most prevalent 31(15.5%). Development of complication is related to the type of the stroke (Hemorrhagic 85% vs Ischemic 51.1%, p<0.05). Conclusion: Complications are common in stroke patients, both medical and neurological complications are predominantly related to hemorrhagic stroke. IAHS Medical Journal Vol 7(2), December 2024; 42-46